Hybridization in heliothine moths: impacts on reproduction, pheromone communication, and pest management - Ivey, Victoria; Hillier, Neil Kirk (Frontiers in Ecology and Evolution, 2023)
Heliothine moths (Family Noctuidae:Subfamily Heliothinae) are ubiquitous crop pests with three documented species combinations known to hybridize: Helicoverpa zea x Helicoverpa armigera, H. armigera x Helicoverpa assulta, and Heliothis virescens x Heliothis subflexa. Hybrids can have advantageous traits, such as increased host range, resistance to insecticides, and increased mating success, posing serious threats to agriculture. However, deleterious traits of hybrids, such as developmental abnormalities or sterility, can be exploited for pest management. In this review, the characteristics of F1 hybrids and backcrosses are examined through a historical lens. Topics reviewed include developmental characteristics, sex pheromone synthesis and perception, mating and calling behavior, sperm morphology, gene expression, electrophysiological responses, structures of the central and peripheral nervous systems, hybrid sterility, and applications in pest control. Recommendations for future studies based on existing gaps of knowledge are given, as are proposed pest management strategies.